2007
DOI: 10.1159/000109969
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide in Hemodialysis Patients: Predictive Value for Hemodynamic Change during Hemodialysis and Cardiac Function

Abstract: Background: Though brain natriuretic peptide (BNP) is widely used as a clinical marker of cardiac function, there is considerable confusion in the interpretation of its value in hemodialysis (HD) patients whose BNPs are often elevated without cardiac diseases. The aim of the present study is to examine the predictive value of BNP for blood pressure (BP) fall during HD and cardiac function. Methods: Subjects consisted of 205 (160 males, 45 females; age 66.5 ± 10.5 years) consecutive uremic patients requiring ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The results of this study revealed that plasma levels of the natriuretic peptides, ANP and BNP, were decreased concomitantly with the decreases in BP variability in the ARB groups. The plasma natriuretic levels are reported to be a good indicator of cardiac function and a sensitive marker of diastolic heart failure even in ESRD patients [35]. The results of this study also showed that baPWV was improved more efficiently concomitantly with the decreases in BP variability in the ARB groups.…”
Section: Discussionsupporting
confidence: 60%
“…The results of this study revealed that plasma levels of the natriuretic peptides, ANP and BNP, were decreased concomitantly with the decreases in BP variability in the ARB groups. The plasma natriuretic levels are reported to be a good indicator of cardiac function and a sensitive marker of diastolic heart failure even in ESRD patients [35]. The results of this study also showed that baPWV was improved more efficiently concomitantly with the decreases in BP variability in the ARB groups.…”
Section: Discussionsupporting
confidence: 60%
“…Our finding of an association between NT-proBNP and GLS or higher NT-proBNP levels predicting worsening GLS had not been reported in patients with ESKD on dialysis in the literature, and it is in keeping with previous investigations in non-ESKD studies [13, 19]. In another study of 205 hemodialysis patients, Matayoshi et al [20] reported that serum BNP concentrations >785 pg/mL predicted LV dysfunction defined by fractional shortening <30% with a sensitivity of 73% and a specificity of 65%. GLS was chosen as the primary outcome as there was evidence suggesting that it is more sensitive than LVEF in detecting cardiac systolic dysfunction and provides incremental prognostic value to LVEF [13, 19].…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have explored the cross‐sectional relationship between NPs as markers of volume overload, in particular bioimpedance analysis or inferior vena cava ultrasound. In our review of 15 pertinent studies, B‐type NPs were significantly associated with measures of hypervolemia (measured by a clinical score, bioimpedance analysis, or inferior vena cava ultrasound) in nine studies (7–15), whereas no relationship was found in 10 (7–9,15–21). Of these 15 studies, four had contrasting findings depending on the outcome measure for volume assessment (7–9,15).…”
Section: What Is the Relationship Between Nps And Markers Of Extracelmentioning
confidence: 93%